Protein-RNA interactions in the active center of transcription elongation complex. - Markovtsov, V (1996)
By using a crosslinkable probe incorporated into the 3' terminus of nascent transcript, three sites were mapped in Escherichia coli RNA polymerase that are contacted by the RNA in the productive elongation complex. Two of these sites are in the beta subunit and one is in the beta' subunit. During elongation, the transcription complex occasionally undergoes an arrest whereby it can neither extend nor release the RNA transcript. It is demonstrated that in an arrested complex, the three contacts of RNA 3' terminus are lost, while a new beta' subunit contact becomes prominent. Thus, elongation arrest appears to involve the disengagement of the bulk of the active center from the 3' terminus of RNA and the transfer of the terminus into a new protein environment.